Views from the Argentinian coast: The fishing community before metropolitan planning - Diego Roldán; Lisandro Arelovich (Íconos)
In this article issues are addressed that are derived from the effects of the disarticulation of local productive processes and the emplacement of a collection of assemblages that seek to rearticulate territories through economies of extractive flows. The objective is to analyze views of a single site on the Argentinian coast with actors operating at multiple scales and how those actors influence the urban, metropolitan, and territorial reconversion and redefinition of that space. In the methodology, a historical approach is combined with documentary and journalistic materials and ethnographic work, with in-depth interviews in the fishing community of Remanso Valerio. The study is divided into four views, with which to reconstruct the following: The history of the occupancy of the neighborhood; the relation of the population with the territory and fishing activities; the impacts of the Paraná-Paraguay waterway and of the Rosario-Victoria bridge; and the relationship between the metropolitan strategic planning and the community. It is concluded that the conflicts between the perspective of the fishing community and that of the people carrying out metropolitan planning come from the asymmetries between actors and scales that shape views of the coast.